PURIFICATION OF 31 AND 67 kDa PROTEIN FRACTION FROM SALIVARY GLAND OF Aedes Albopictus (SKUSE) (DIPTERA: CULLICIDAE) - Syubbanul Wathon; Rike Oktarianti; Nuril Azizah; Yasir Mubarok; Riana Agatha Listiani; Kartika Senjarini (BIOEDUKASI, 2021)
Aedes albopictus mosquito is a potential vector for Dengue Haemorrhagic Fever (DHF) which transmits Dengue virus during blood feeding. The success of the blood feeding process is aided by the biological activity of proteins in the salivary glands of Aedes albopictus. There are 30 types of proteins from the salivary glands of Aedes albopictus which are carried along blood feeding process. Proteins in the salivary glands act as vasodilator and immunomodulator. Previous studies have identified two immunogenic proteins from the salivary glands of Aedes albopictus with molecular weight of 31 and 67 kDa. Further research on the biological function of these proteins requires its purified protein to better specify the target to developing a dengue vaccine. The objective of this study was to obtain 31 and 67 kDa purified proteins by implementation of electroelution and dialysis purification. The 31 and 67 kDa protein was successfully purified by this method. This has been confirmed by a single band visualization after SDS-PAGE analysis